Raman Spectra of Bulk and Few-Layer GeSe From First-Principles Calculations - Zhao, Yi-Feng; Guan, Zhao; Zhong, Ni; Yue, Fang-Yu; Xiang, Ping-Hua; Duan, Chun-Gang (Frontiers in Materials, 2021)
Raman spectra play a significant role in the study of polar materials. Herein, we report the influence of strain and interlayer shift on vibration responses in bulk and few-layer ferrovalley material GeSe in different polarization states (ferroelectric/FE and antiferroelectric/AFE) based on density functional theory and density functional perturbation theory calculations. We find Ag1 mode shifts by about 10 cm-1 from monolayer to bilayer and trilayer due to the interlayer coupling. The Ag3 mode on behalf of FE mode is observed that is consistent with the experiments in bulk and few-layer GeSe. Meanwhile, in our calculations, with the transition between AFE and FE state in the bilayer and trilayer, the Raman intensity of Ag2 and Ag3 mode decrease obviously whereas that of Ag1 mode increases. Interestingly, the Raman peaks shifted a lot due to the strain effect. We expect these variations in the Raman spectroscopy can be employed to identify the status of GeSe films, e.g., the AFE or FE state, and the number of layers in experiments.